CK2α-mediated phosphorylation of DUB3 promotes YAP1 stability and oncogenic functions - Lei Huang; Yalei Wen; Qin Guo; Caishi Zhang; Xiao Yang; Mei Li; YiXia Liu; Xinying Li; Jiaxin Tang; Xiaofeng Zhou; Qi Qi; Haoxing Zhang; et al. (Cell Death and Disease)
Abstract The aberrant upregulation of Yes-associated protein 1 (YAP1) in a variety of solid cancers contributes to tumor progression and poor clinical outcomes, rendering it an appealing therapeutic target. However, effective therapies to directly target YAP1 remain challenging. In this study, we perform a high-throughput screening and identify Casein kinase II (CK2) as an uncharacterized upstream regulator of YAP1 turnover in cancer cells of ovarian cancer and several other cancer types. Pharmacological inhibition of Casein kinase II by Silmitasertib or genetic depletion of the catalytic subunit of Casein kinase II (CK2α) markedly destabilizes YAP1 and consequently suppresses its oncogenic functions in vitro and in vivo. Moreover, we reveal that DUB3 as a bona fide deubiquitinase of YAP1, which functionally links CK2 and YAP1 stability in a variety of human cancers. Mechanistically, CK2α directly phosphorylates DUB3 at Thr495, thereby facilitating DUB3-mediated deubiquitination process of YAP1. On the contrary, the loss of Thr495 phosphorylation by the phosphorylation-defective mutant DUB3 T495A, the cancer-related mutant DUB3 D496H and CK2 inhibition failed to deubiquitinate and stabilize YAP1 effectively. Notably, upregulated expressions of CK2α and DUB3 in ovarian cancer positively correlate with YAP1 overexpression. Collectively, our findings demonstrate the functional significance of the CK2α-DUB3 axis in YAP1 stabilization and YAP1-driven tumor progression, highlighting that strategies to target this axis might be of benefit in the clinical management of ovarian cancer and several other lethal cancers with aberrantly upregulated YAP1.